2005
DOI: 10.1128/aem.71.8.4801-4808.2005
|View full text |Cite
|
Sign up to set email alerts
|

Optically Transparent Porous Medium for Nondestructive Studies of Microbial Biofilm Architecture and Transport Dynamics

Abstract: We describe a novel and noninvasive, microscopy-based method for visualizing the structure and dynamics of microbial biofilms, individual fluorescent microbial cells, and inorganic colloids within a model porous medium. Biofilms growing in flow cells packed with granules of an amorphous fluoropolymer could be visualized as a consequence of refractive index matching between the solid fluoropolymer grains and the aqueous immersion medium. In conjunction with the capabilities of confocal microscopy for nondestruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 49 publications
3
58
0
Order By: Relevance
“…The empirical parameter γ can be used to quantify the important role of macroscopic hydrodynamic and chemical effects on clogging ( Figure 5), but continued progress toward a mechanistic understanding of deposit morphology, extending the work of Veerapaneni and Wiesner (36), will require experimental techniques that non-invasively quantify deposit structure (e.g. , 39,40 ). This effort, in turn, would provide the basis for improved pore-scale clogging models.…”
Section: Hydrodynamic Shearmentioning
confidence: 99%
“…The empirical parameter γ can be used to quantify the important role of macroscopic hydrodynamic and chemical effects on clogging ( Figure 5), but continued progress toward a mechanistic understanding of deposit morphology, extending the work of Veerapaneni and Wiesner (36), will require experimental techniques that non-invasively quantify deposit structure (e.g. , 39,40 ). This effort, in turn, would provide the basis for improved pore-scale clogging models.…”
Section: Hydrodynamic Shearmentioning
confidence: 99%
“…To manufacture a 3D porous material that is geometrically similar to soil, we used granules made from the fluoropolymer Nafion, which is transparent in water and thus allows microscopic imaging deep inside the porous material (47). Nafion granules were generated from dissolved Nafion (Ion Power).…”
Section: Methodsmentioning
confidence: 99%
“…The standard planktonic bacterial physiology is typically exemplified by free-living single bacteria with optimal nutrition, gas exchange and agitation (typically 250 rpm) [24,25]. In contrast, the biofilm physiology has multicellular differentiation, multicellular communication, internal architecture and rudimentary fluid transport systems [26,27]. Shah et al [4] reported on the antibacterial activity of SLs in various carbohydrate-containing media against a selection of Gram-positive and Gram-negative bacteria, in our study we selected Cupriavidus necator ATCC 17699 and…”
Section: Discusionmentioning
confidence: 99%